Osteosynthesis distal tibial metadiaphyseal fractures with intramedullary nailing versus plating - Vashisht, Deepak; Daroch, Manjit S.; Sreen, Sanjeev; Rathi, Kuldeep (International Journal of Research in Medical Sciences, 2017)
Background: The management of the tibial fracture remains controversial despite advances in both non-operative and operative care. Plates and intramedullary nails are two well-accepted and effective methods, but each has been historically related to complications. The present study was conducted to compare the results of displaced extra-articular distal tibia meta-diaphyseal fractures OTA/AO Type 42A- C (distal) and 43-A treated with intramedullary nailing versus plating with respect to union of fracture, early Restoration of function, the axial alignment and Complications, if any. Methods: In this study 30 patients of extra-articular distal tibia fracture AO type 42 A-C (distal) and 43 A were randomly selected and 15 were operated with intramedullary nailing and remaining 15 with plating. The patients were regularly followed up for a period of 9 months with radiological and clinical examination. Final assessment was done by Tenny and Wiss clinical assessment criteria. Results: In Interlocking group, average time for union was 20.33 weeks in Interlocking nail group compared to 23.21 weeks in plating group which was significant (p value 0.011). Also, the average time required for partial and full weight bearing in the nailing group was 7.2 weeks and 13.2 weeks respectively which was significantly less as compared to 9.33 weeks and 16.64 weeks in the plating group. Lesser complications in terms of implant irritation, ankle stiffness and infection (superficial and deep) were seen in Interlocking group as compared to plating group. Conclusions: In present study ILN showed better outcome as it offers advantage in terms of mean operating time, less invasive surgery, hospital stay, partial and full weight bearing time and union time.